2023
DOI: 10.1002/wat2.1650
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater surveillance could serve as a pandemic early warning system for COVID‐19 and beyond

Abstract: Wastewater-based surveillance can be used as an early warning system to identify COVID-19 outbreaks because the viral load can be observed in sewage before it is clinically verified. Wastewater surveillance of SARS-CoV-2 can trace the transmission dynamics of infection in communities when using the scale of a wastewater diversion and treatment system. Using this early detection method can help protect human health and mitigate socio-economic losses. It can help quantify the epidemiological data of a given popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…Substantial research has probed into the correlations between SARS-CoV-2 marker genes present in wastewater and the incidence and prevalence of COVID-19 cases in various sewersheds, with the goal of establishing a predictive model for estimating present and future COVID-19 cases. The focus has been on exploring the wastewater surveillance as an early warning system for pandemics, underscoring its capacity to provide diverse lead times before the clinical detection of cases [ [15] , [16] , [17] ]. The lead time is identified as the difference in time between when an increase in viral detection is observed in wastewater and when a corresponding increase in clinical cases is reported [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research has probed into the correlations between SARS-CoV-2 marker genes present in wastewater and the incidence and prevalence of COVID-19 cases in various sewersheds, with the goal of establishing a predictive model for estimating present and future COVID-19 cases. The focus has been on exploring the wastewater surveillance as an early warning system for pandemics, underscoring its capacity to provide diverse lead times before the clinical detection of cases [ [15] , [16] , [17] ]. The lead time is identified as the difference in time between when an increase in viral detection is observed in wastewater and when a corresponding increase in clinical cases is reported [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous use cases for how wastewater monitoring has been used by public health officials for decision-making have been demonstrated, including as an early warning system that can indicate disease trends and hospitalizations before other surveillance data (e.g. clinical testing) [1][2][3][4][5][6][7] , as a source of information on disease trends where there is limited case data 6,[8][9][10][11] , and as a tool for detecting localized outbreaks within communities [12][13][14][15][16][17][18][19][20][21] and facilities [22][23][24][25][26][27][28][29][30][31] . Another important use case for wastewater monitoring is to detect vaccine-preventable diseases and direct immunization resources.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 virus, which is about 100 nm in size, is mainly spreading in air through respiratory droplets released by coughing, sneezing or talking (Wang et al 2021). Studies (Gormley et al 2020;Angga et al 2023;Gahlot et al 2023) have suggested that drainage systems are also a potential route of virus transmission. When virus-laden faeces are discharged into drainage systems, large numbers of tiny and virus-laden droplets are produced by the wastewater falling, impacting and splashing.…”
Section: Introductionmentioning
confidence: 99%